Genetically-Guided Medical Nutrition Therapy in Type 2 Diabetes Mellitus and Pre-diabetes: A Series of n-of-1 Superiority Trials - Gkouskou, Kalliopi K.; Grammatikopoulou, Maria G.; Lazou, Evgenia; Sanoudou, Despina; Goulis, Dimitrios G.; Eliopoulos, Aristides G. (Frontiers in Nutrition, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a heterogeneous metabolic disorder of multifactorial etiology that includes genetic and dietary influences. By addressing the latter, medical nutrition therapy (MNT) contributes to the management of T2DM or prediabetes towards achieving glycaemic control and improved insulin sensitivity. However, the clinical outcomes of MNT vary and may further benefit from personalized nutritional plans that take into consideration genetic variations associated with individual responses to macronutrients. The aim of the present series of n-of-1 trials was to assess the effects of genetically-guided versus conventional MNT on patients with prediabetes or T2DM. Methods: A quasi-experimental cross-over design was adopted in three Caucasian adult men with either diagnosis. Complete diet, bioclinical and anthropometric assessment was performed and a conventional MNT, based on clinical practice guidelines was applied for 8 weeks. After a week of “wash-out”, a precision MNT was applied for an additional 8 week period based on the genetic characteristics of each patient. Outcomes of interest included changes in body weight (BW), fasting plasma glucose (FPG) and blood pressure (BP). Results: Collectively, the trials indicated improvements in BW, FPG, BP and glycosylated haemoglobin (HbA1c) following the genetically-guided precision MNT intervention. Moreover, both patients with prediabetes experienced remission of the condition. Conclusions: Improved BW loss and glycemic control can be achieved in patients with prediabetes/T2DM by coupling MNT to their genetic makeup, guiding optimal diet, macronutrient composition, exercise and oral nutrient supplementation in a personalized manner.